Functional expression of a human Na+/H+ antiporter gene transfected into antiporter-deficient mouse L cells. - Franchi, A (1986)
To clone the gene for the human Na+/H+ antiporter, we first constructed a stable mouse LTK- cell line (LAP1) lacking Na+/H+ antiport activity. Second, we devised a selective technique based on acid killing that specifically sorts out cells expressing low levels of Na+/H+ antiport activity from a population of antiporter-deficient cells (AP-). LAP1 cells (TK- and AP-) were cotransformed with human genomic DNA and the thymidine kinase (TK) gene. TK+ transformants, first selected, were submitted to acid loading. The rare transformants that survived (frequency, 2-8 X 10(-7) expressed Na+/H+ antiport activity (AP+). We found that: transformation with mouse LAP1 DNA did not give rise to AP+ transformants; transformation of LAP1 cells with DNA from an altered Na+/H+ antiporter hamster variant led to AP+ transformants expressing the altered Na+/H+ antiporter of the DNA donor; human repeated sequences were present in all primary, secondary, and tertiary mouse AP+ transformants; six identical EcoRI human DNA fragments (55 kilobase pairs of the human genome) cosegregated with the Na+/H+ antiport activity in secondary and tertiary transformants. These results strongly suggest that we have stably expressed the structural gene for the human Na+/H+ antiporter in mouse cells.